Effects of Kalimeris indica (L.) Sch Bip on colitis-associated colorectal cancer - Wang, Mo-Fei; Li, Hao; Cui, Jian; Chen, Yu-Han; Cui, Yong (Frontiers in Pharmacology, 2023)
Kalimeris indica (L.) Sch Bip (K. indica) is a plant of the genus Kalimeris in Asteraceae, and its whole herb can be used as medicine for the treatment of intestinal inflammatory diseases. But the mechanism is not clear. Therefore, this study was designed to explore the mechanism of K. indica (KI) in colitis-associated colorectal cancer. The expression levels of miR-31-5p and proinflammatory factors were detected using THP-1 and Caco2 cells in vitro. KI could rescue the upregulation of miR-31-5p induced by IL-6 and TNF-α in Caco2 and THP-1 cells. In LPS-stimulated PMA-differentiated THP-1 cells, KI restored miR-31-5p expression by downregulating the expression of IL-6 and TNF-α. C57BL/6 mice were used to construct CAC model through the induction of azoxymethane/dextran sulfate sodium. The successfully established CAC mice were treated with water extract of KI through intragastric administration for 5 weeks. The result showed that KI could significantly reduce the atypical hyperplasia in colon tissue, and inhibit the expression of proinflammatory factors such as IL-6, TNF, IL-11, IL-7, etc. At the same time, KI could restore the level of miR-31-5p in mice, and therefore the downstream LATS2 to inhibit the development of CAC. These above results indicate that KI is a potentially effective herb medicine to prevent CAC.